The Influence of Using Learning Media Assisted by Smart Apps Creator (SAC) on Students Cognitive Learning Outcomes on the Human Circulatory System Material - Djano, Apriyansah; Latjompoh, Masra; Uloli, Ritin; Abdjul, Tirtawaty; Ntobuo, Nova Elysia; S.Payu, Citron (Jurnal Pijar Mipa, 2025)
This research aims to determine the effect of using learning media assisted by Smart Apps Creator (SAC) on students' cognitive learning outcomes on the human circulatory system material at SMP Negeri 2 Suwawa. The research method used in this study was an experiment using a One Group Pretest-Posttest Design with a population of all VIII grade students of SMP Negeri 2 Suwawa. The sample consists of 3 classes, namely the experimental class, replication 1 and replication 2, with a purposive sampling technique. Data was obtained by statistical tests and inferential statistics, including normality tests, hypothesis tests, and N-Gain analysis. The results of the average acquisition of class VIII students were greater than the KKTP, shown by the average value of the experimental class of 84.48, replication class 1, 81.14 and replication class 2, 86.45, compared to the KKTP of 75. Based on the hypothesis testing criteria, where the t count in the experimental class was 10.969 compared to the t table of 2.045, replication class 1 obtained a t count of 6.710 with a t table of 2.074, and replication class 2 obtained a t count of 9.569 with a t table of 2.093. It can be concluded that the hypothesis testing in the three classes is that the tcount is greater than the ttable. This can be interpreted as the use of learning media assisted by Smart Apps Creator influences students' cognitive learning outcomes.